Katzung & Trevor's pharmacology : examination & board review - Trevor, Anthony J.; Kruidering-Hall, Marieke (New York : McGraw-Hill Education, 2015)
From the authors of Basic and Clinical Pharmacology, the leading pharmacology textbook, here is the newest edition of the best review book available for medical pharmacology course exams and board examinations
PART I: BASIC PRINCIPLES -- Chapter 1: Introduction -- Chapter 2: Pharmacodynamics -- Chapter 3: Pharmacokinetics -- Chapter 4: Drug Metabolism -- Chapter 5: Pharmacogenomics -- PART II: AUTONOMIC DRUGS -- Chapter 6: Introduction to Autonomic Pharmacology -- Chapter 7: Cholinoceptor-Activating & Cholinesterase-Inhibiting Drugs -- Chapter 8: Cholinoceptor Blockers & Cholinesterase Regenerators -- Chapter 9: Sympathomimetics -- Chapter 10: Adrenoceptor Blockers -- PART III: CARDIOVASCULAR DRUGS -- Chapter 11: Drugs Used in Hypertension -- Chapter 12: Drugs Used in the Treatment of Angina Pectoris -- Chapter 13: Drugs Used in Heart Failure -- Chapter 14: Antiarrhythmic Drugs -- Chapter 15: Diuretics & Other Drugs That Act on the Kidney -- PART IV: DRUGS WITH IMPORTANT ACTIONS ON SMOOTH MUSCLE -- Chapter 16: Histamine, Serotonin, & the Ergot Alkaloids -- Chapter 17: Vasoactive Peptides -- Chapter 18: Prostaglandins & Other Eicosanoids -- Chapter 19: Nitric Oxide, Donors, & Inhibitors -- Chapter 20: Drugs Used in Asthma & Chronic Obstructive Pulmonary Disease -- PART V: DRUGS THAT ACT IN THE CENTRAL NERVOUS SYSTEM -- Chapter 21: Introduction to CNS Pharmacology -- Chapter 22: Sedative-Hypnotic Drugs -- Chapter 23: Alcohols -- Chapter 24: Antiseizure Drugs -- Chapter 25: General Anesthetics -- Chapter 26: Local Anesthetics -- Chapter 27: Skeletal Muscle Relaxants -- Chapter 28: Drugs Used in Parkinsonism & Other Movement Disorders -- Chapter 29: Antipsychotic Agents & Lithium -- Chapter 30: Antidepressants -- Chapter 31: Opioid Analgesics & Antagonists -- Chapter 32: Drugs of Abuse -- PART VI: DRUGS WITH IMPORTANT ACTIONS ON BLOOD, INFLAMMATION, & GOUT -- Chapter 33: Agents Used in Cytopenias; Hematopoietic Growth Factors -- Chapter 34: Drugs Used in Coagulation Disorders -- Chapter 35: Agents Used in Dyslipidemia -- Chapter 36: NSAIDs, Acetaminophen, & Drugs Used in Rheumatoid Arthritis & Gout -- PART VII: ENDOCRINE DRUGS -- Chapter 37: Hypothalamic & Pituitary Hormones -- Chapter 38: Thyroid & Antithyroid Drugs -- Chapter 39: Corticosteroids & Antagonists -- Chapter 40: Gonadal Hormones & Inhibitors -- Chapter 41: Pancreatic Hormones, Antidiabetic Agents, & Glucagon -- Chapter 42: Drugs That Affect Bone Mineral Homeostasis -- PART VIII: CHEMOTHERAPEUTIC DRUGS -- Chemotherapeutic Drugs: Introduction -- Chapter 43: Beta-Lactam Antibiotics & Other Cell Wall Synthesis Inhibitors -- Chapter 44: Chloramphenicol, Tetracyclines, Macrolides, Clindamycin, Streptogramins, & Linezolid -- Chapter 45: Aminoglycosides -- Chapter 46: Sulfonamides, Trimethoprim, & Fluoroquinolones -- Chapter 47: Antimycobacterial Drugs -- Chapter 48: Antifungal Agents -- Chapter 49: Antiviral Chemotherapy & Prophylaxis -- Chapter 50: Miscellaneous Antimicrobial Agents & Urinary Antiseptics -- Chapter 51: Clinical Use of Antimicrobials -- Chapter 52: Antiprotozoal Drugs -- Chapter 53: Antihelminthic Drugs -- Chapter 54: Cancer Chemotherapy -- Chapter 55: Immunopharmacology -- PART IX: TOXICOLOGY -- Chapter 56: Environmental & Occupational Toxicology -- Chapter 57: Heavy Metals -- Chapter 58: Management of the Poisoned Patient -- PART X: SPECIAL TOPICS -- Chapter 59: Drugs Used in Gastrointestinal Disorders -- Chapter 60: Dietary Supplements & Herbal Medications -- Chapter 61: Drug Interactions -- Appendix I: Strategies for Improving Test Performance -- Appendix II: Key Words for Key Drugs
"A Lange medical book."
Includes bibliographical references index
Keywords: Health & Biological Sciences; Examinations